THE STRUGGLES OF THE SENIOR HIGH SCHOOL STUDENTS TO COPE WITH ONLINE EFL LEARNING DURING PANDEMIC OF COVID-19 - Vemi Maulidiawati; Martina Mulyani (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2021)
The research described here investigates the experience of the students in online learning during COVID-19 Pandemic. Methods of the investigation was qualitative case study approach involving two students from different Senior High Schools in Cimahi. This research specifically focused on the struggle of students in online EFL learning. The analysis of the students’ observation, interview and documentation revealed some strategies they used to overcome their problems. Results discovered that the Pandemic had made the students experienced uncertain learning journey. The online learning provided special challenges for the students and some strategies showed the important role of student agency in making them stay motivated.